2019
DOI: 10.1016/j.niox.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute dietary nitrate supplementation on aortic blood pressures and pulse wave characteristics in post-menopausal women

Abstract: Purpose: Consumption of nitrate-rich beetroot juice can lower blood pressure in peripheral as well as central arteries and may exert additional hemodynamic benefits (e.g. reduced aortic wave reflections). The specific influence of nitrate supplementation on arterial pressures and aortic wave properties in postmenopausal women, a group that experiences accelerated increases in these variables with age, is unknown. Accordingly, the primary aim of this study was to determine the effect of consuming nitrate-rich b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
3
14
0
Order By: Relevance
“…In line with previous studies (Kelly et al., 2013; Kim et al., 2019), baseline MAP decreased following nitrate supplementation (Figure 1). During heat stress, MAP remained relatively unchanged in BRJ but progressively declined in CON (Figure 5).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies (Kelly et al., 2013; Kim et al., 2019), baseline MAP decreased following nitrate supplementation (Figure 1). During heat stress, MAP remained relatively unchanged in BRJ but progressively declined in CON (Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…The magnitude of change in baseline NO metabolite levels and arterial pressures with nitrate supplementation is consistent with previous studies (Kelly et al., 2013; Kim et al., 2019; Wylie et al., 2013); however, the responses of two participants, both of whom reported 100% compliance to the beetroot juice intervention, are deserving of closer inspection. For one female participant, plasma NOx increased to a far lesser extent than the remaining participants, with a post‐supplementation value of 227.8 μmol l −1 compared to an average of 512.1 μmol l −1 among the remaining participants.…”
Section: Discussionsupporting
confidence: 88%
“…A study by Kim et al (2019) specifically demonstrated aortic SBP and mean BP reduction, after BRJ consumption, in postmenopausal women. BRJ did not restore aortic wall stiffness in these women (Kim et al 2019).…”
Section: Effect On Blood Pressurementioning
confidence: 99%
“…While most studies investigated BP reduction in younger to middle-aged adults, Raubenheimer et al (2017) also found BP reduction directly after BRJ consumption in healthy elderly people (Raubenheimer et al 2017). A study by Kim et al (2019) specifically demonstrated aortic SBP and mean BP reduction, after BRJ consumption, in postmenopausal women. BRJ did not restore aortic wall stiffness in these women (Kim et al 2019).…”
Section: Effect On Blood Pressurementioning
confidence: 99%
“…While historically the oxidation of endogenous l -arginine was thought to be the primary source of nitric oxide production, recently an enterosalivary circuit has been identified wherein ingested nitrate (from, e.g., leafy greens, beetroot) are reduced to nitrite by bacteria in the oral cavity and subsequently to nitric oxide in systemic circulation [ 17 ]. Compelling evidence in humans have shown reduced blood pressure [ 18 , 19 ], enhanced endothelial-dependent vasodilation [ 20 ] and improved exercise performance [ 21 ] with dietary nitrate supplementation. However, the feasibility of dietary nitrate supplementation combined with habitual exercise training is largely unknown in older populations.…”
Section: Introductionmentioning
confidence: 99%